Propuesta para el desarrollo de una red de consultorios modulares de telemedicina orientados a la mejora de servicios de salud para pacientes con enfermedades crónicas no transmisibles en ESSALUD - Bosio Bobadilla, José Luis (2024)
In 2020, the COVID-19 pandemic exacerbated problems of access to and quality of health services. However, this experience left us with telemedicine as a tool and operational process, achieving a total of 9.3 million medical visits in EsSalud alone during the first 11 months of 2021 (Social Health Security, 2021). Today, in 2023, telemedicine continues to play an important role as an additional package of hospitals, centers and posts. However, the telemedicine strategy implies certain conditions for its application, such as the use of Information and Communication Technologies (ICT). Without the internet and a device, the doctor-telemedicine-patient trinomial becomes unsustainable, becoming even more difficult in places where there is no coverage of health services, such as in rural areas where only 8% of households have access to the internet (National Institute of Statistics and Informatics – INEI, 2020). Based on the existing telemedicine network, its processes and standards, this study proposes a solution that meshes the current supply with the unmet demand through a network of modular clinics equipped for telemedicine care that travel through different locations in Peru covering the services demanded by each population. However, in addition to the technical requirements on the part of the patient to connect to telemedicine care, the role of health personnel in the implementation of the proposal plays an important role, therefore, through Davis' (1989) technology acceptance model, the determinants of health professionals' satisfaction in relation to the telemedicine service in hospitals in Peru will be investigated and analyzed. so that in this way they are taken into consideration for the success of the implementation of the proposal.